2017
DOI: 10.1155/2017/5912940
|View full text |Cite
|
Sign up to set email alerts
|

Interrelations among SMED Stages: A Causal Model

Abstract: Mexico has received a lot of foreign investment that has brought in a wide range of novel production philosophies, such as Single Minute Exchange of Dies (SMED). Despite its popularity and reported effectiveness, Mexican companies often quit SMED implementation as they consider it challenging. This usually happens when organizations are not familiarized enough with each one of the SMED stages or do not know how they are interrelated. In this article the interrelations among the different SMED implementation st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…It is recommended to capture the actions performed by the machine operator and the steps or the operations performed by the machine during the changeover. Usually, the actual optimization involves the actions performed by the operator [34]. It is also recommended to record the changeover without making any comments in order to capture the actual performance of the changeover.…”
Section: Step One -Identify Elements -Identification Stagementioning
confidence: 99%
See 1 more Smart Citation
“…It is recommended to capture the actions performed by the machine operator and the steps or the operations performed by the machine during the changeover. Usually, the actual optimization involves the actions performed by the operator [34]. It is also recommended to record the changeover without making any comments in order to capture the actual performance of the changeover.…”
Section: Step One -Identify Elements -Identification Stagementioning
confidence: 99%
“…During the third step, the effort should be made to transform internal changeover processes into external ones. At the same time, each change should be carefully examined in regard to costs and labor needed for the change to be implemented, balanced against the benefits the time-saving the change will bring [34]. Each element within the changeover procedure should be looked at, and the most promising elements should be prioritized.…”
Section: Step Three -Convert Internal Elements To External -Transformation Stagementioning
confidence: 99%
“…SMED is a response to the need to reduce production batches' size and looks to switch quickly from one product to another [49]. Traditionally, manufacturers prefer to assemble large quantities and prorate the setup cost over a high number of units.…”
Section: Single-minute Exchange Of Die (Smed)mentioning
confidence: 99%
“…The model illustrated in Figure 1 is tested using the structural equations modeling (SEM) technique based on partial least squares (PLS) and integrated in WarpPLS 6 ® software program, which is recommended for ordinal, non-normal data and small samples [65], and similar research has been performed using these techniques, such as, for example, Díaz-Reza, et al [66], who related the SMED stages to the benefits gained, and Boon Sin, et al [67], who reported the relationship between knowledge management and six sigma success. The indices and parameters for model validation were obtained with a 95% confidence level.…”
Section: Model Evaluationmentioning
confidence: 99%